difference of the cubic
a^3 - b^3 = (a-b)(a^2 + ab + b^2)
3^3x^3 - 2^3
(3x)^3 - 2^3
(3x - 2) (9x^2 + 6x + 4)
2007-03-25 17:29:35
·
answer #1
·
answered by 7
·
1⤊
1⤋
27x^3 - 8 = (3x - 2)(9x^2 + 6x + 4)
2007-03-26 01:17:52
·
answer #2
·
answered by Sherman81 6
·
0⤊
0⤋
That is easy. This is the difference of a perfect cube. (3x-2)(9x^2+6x+4)
2007-03-26 00:32:28
·
answer #3
·
answered by Kristian 2
·
1⤊
0⤋
(3x-2)(9x^2 + 6x + 4)
there's a formula for this. like there's the (a^2-b^2)=(a+b)(a-b)
this one's (a^3 - b^3) = (a-b)(a^2 + ab + b^2).
and (a^3 + b^3) = (a+b)(a^2 - ab + b^2)
Hope that helped
2007-03-26 00:32:57
·
answer #4
·
answered by Anonymous
·
1⤊
0⤋
a³ - b³ = (a - b).(a² + ab + b²)
a = 3x and b = 2
a³ - b³ = (3x - 2).(9x² + 6x + 4)
2007-03-26 05:25:18
·
answer #5
·
answered by Como 7
·
0⤊
0⤋
all of them are right except for Juni Mcc
2007-03-26 00:35:07
·
answer #6
·
answered by Ha!! 2
·
0⤊
0⤋
(3x-2)^3=0
x=2/3
I hope this helps. :)
2007-03-26 00:30:21
·
answer #7
·
answered by Juni Mccoy 3
·
0⤊
2⤋